A child with ulcerative colitis presenting with delirium: a case report - Akbulut, Ulaş Emre; Işık, İshak Abdurrahman and Atalay, Atike and Kutluk, Gültekin and İnal, Gülşah (The Turkish Journal of Pediatrics, 2025)
Background. Delirium in patients with ulcerative colitis may be seen, especially in the elderly and in patients hospitalized for a long time. In children, Wernicke’s encephalopathy may occur due to thiamine deficiency in both ulcerative colitis and Crohn’s disease. We present a patient with ulcerative colitis who presented with delirium as the first symptom, did not respond to steroid treatment and improved with anti-tumor necrosis factor-alpha treatment. Case Presentation. A 14-year-old male child presented with complaints of nonsensical speech and hallucinations for two days. He also had 2-3 loose, non-bloody stools per day. Neurological examination was normal. There was no electrolyte abnormality or vitamin deficiency. The patient’s diarrhea gradually increased and became bloody, and was ultimately diagnosed with ulcerative colitis. The patient, who did not respond to steroid treatment, completely recovered with anti-tumor necrosis factor treatment. Conclusions. We report a patient with ulcerative colitis who presented with delirium as the first symptom. The absence of electrolyte imbalance or vitamin deficiency in our patient suggests that inflammation is the cause of this condition. To the best of our knowledge, this is the first description of the relationship between inflammatory bowel disease and delirium in children.